(untitled) (Proceedings of Southern Federal University. Philology, 2015)
The article “On the role of ethnic and folklore traditions in North Caucasus novel” is devoted to the study of the role and place of artistic, ethnographic and myth-folklore traditions in the genre of the novel. The analysis is carried out on the material of the Ossetian writer E. Uruymagova “Towards life”. The paper discusses in detail folklore and myth and epic themes in the literature of the region and it is determined by the impact of ethnic and folk traditions in the work of writers. The novel “Towards Life” is analyzed in the ratio of independent art systems - literature and folklore, taking into consideration that the ethno-folk traditions in the national Romanist is one of the ways to enrich its poetics. Key words: novel, myth, folklore traditions, artistic ethnographism, symbolism. Musukaeva Andgella Hamitovna - Kabardino-Balkarsky state university, Institute of linguistics, Russian and Foreign literature dpt. Ph.D. of linguistics, professor. Head of Russian and Foreign literature dpt. Tel.: 8(8552) 47-44-04; 8-938-692-73-43